Broad-scope management accounting information, innovation and performance: Empirical evidence from Vietnam - Le Mong Huyen; Nguyen Thi Thu; Hoang Cam Trang (My University, 2020)
Broad-scope management accounting information, innovation and performance: Empirical evidence from Vietnam
Keywords: Broad-scope information; Innovation; Firm performance